2002
DOI: 10.1103/physreve.65.036402
|View full text |Cite
|
Sign up to set email alerts
|

Theory ofKαgeneration by femtosecond laser-produced hot electrons in thin foils

Abstract: An analytical model of femtosecond K(alpha) x-ray generation from laser-irradiated foils is presented. Expressions are found for the photon emission yield in both forward and backward directions in integral form as a function of hot-electron temperature and target thickness. It is found that for any given target material, there is a foil thickness and a hot-electron temperature at which the K(alpha) emission is maximized. Conversion efficiencies are consistent with contemporary measurements of K(alpha) radiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(31 citation statements)
references
References 24 publications
1
29
0
1
Order By: Relevance
“…The scaling of Reich et al 13 from particle-in-cell simulations of similar laser pulses gives T hot = 110͑I 17 ͒ 1/2 keV, where I 17 means the intensity in units of 10 17 W cm −2 . In that and similar works, 14,15 it has been shown that for a given energy into fast electrons the optimum K␣ production in a Cu slab rises swiftly as T hot approaches ϳ50 keV with a slow decay at higher temperature caused by fewer hot electrons and deeper penetration into the target where K␣ photons are reabsorbed. For our case, this optimum is reached at I ϳ 2 ϫ 10 16 W cm −2 and this is the average irradiance at an offset of ϳ420 m. For constant absorption, we would expect a broad peak in K␣ at this offset.…”
mentioning
confidence: 68%
“…The scaling of Reich et al 13 from particle-in-cell simulations of similar laser pulses gives T hot = 110͑I 17 ͒ 1/2 keV, where I 17 means the intensity in units of 10 17 W cm −2 . In that and similar works, 14,15 it has been shown that for a given energy into fast electrons the optimum K␣ production in a Cu slab rises swiftly as T hot approaches ϳ50 keV with a slow decay at higher temperature caused by fewer hot electrons and deeper penetration into the target where K␣ photons are reabsorbed. For our case, this optimum is reached at I ϳ 2 ϫ 10 16 W cm −2 and this is the average irradiance at an offset of ϳ420 m. For constant absorption, we would expect a broad peak in K␣ at this offset.…”
mentioning
confidence: 68%
“…According to D. Salzmann's model [13], the absolutely K is given as a function of TE and the hot electron temperature T h :…”
Section: Transfer Efficiencymentioning
confidence: 99%
“…Assuming a single Maxwellian electron velocity distribution and one-way travel of hot electrons through the cone, energy transfer efficiency (TE) of incident LFEX laser to hot electrons was derived according to Salzmann's model [13]. Figure 3 shows the TE given as a function of hot electron temperatures.…”
Section: K Line Measurement For Au-cone-guided Targetsmentioning
confidence: 99%